IMPROVEMENT OF THE SYSTEM OF BOARDING CARE AND EDUCATION IN UKRAINE IN THE CONTEXT OF INTERNATIONAL EXPERIENCE - Філик, Наталія Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: the purpose of this article is to explore current challenges in the system of boarding care and education in Ukraine with reference to analyses of foreign experiences in addressing the reform of boarding education. Methods used include comparative legal analysis, objective truth, cognitive analytical analysis and other approaches. Results focus on generalised mechanisms of reforming boarding education in accordance with modern challenges in the educational field. Proposed changes to the legislation are to be in accordance with international standards. Discussion: the discussion clarified the normative consolidation of the reform of boarding care and education with particular reference to the generalised experience of reforming boarding schools in the EU. This guided proposed changes to current legislation. We believe that Ukraine should make every effort to reform the system of boarding schools by expanding the network of other forms of child rearing as a foster care, foster families and family-type orphanages. In carrying out such reforms, reference should be made to the experience of countries such as Poland and Bulgaria, which had similar systems and today have successful experience in reforming the childcare system. Accordingly, we believe that Poland’s experience in involving family members and relatives in foster families, shifting the emphasis to family education with the assistance of the state, minimizing boarding education is important experience in this area and can be borrowed to reform boarding education in Ukraine, which must meet world standards of care for orphans and children deprived of parental care. Another issue that needs to be addressed concerns surrogacy. In the absence of proper regulation of this phenomenon, there are relevant violations and abuses in this area, as well as the formation of attitudes towards children as a commodity, which is negatively reflected in society as a whole. In the context of our study, there are known facts when, for various reasons, parents (diseases and birth defects) abandon individual children and they remain in the boarding school system. Therefore, we believe that the prohibition of surrogacy, as a common practice of Ukrainian society, will change the attitude towards children as a commodity and strengthen their protection at the national and international levels, because, as a rule, in most countries such practice is either prohibited or significantly limited.